Characteristics genotipics and fenotipics in athletics sprinters - Leonardo Chrysostomo dos Santos; Paulo Moreira Silva Dantas; José Fernandes Filho (Desafio Singular, 2008)
The purpose this study was to comparate the genotipics and the phenotipics characteristics in a group of the runners sprint. They were part 19 athletes of both sexes and describe for 22,42±3,53 age, 66,61±7,66kg body mass and 173,18±7,23cm weight. The genetic profile and the somatotype were based in Cummins & Midlo (1961) and Heath & Carter (1990) respectively, and the evaluation isokinetic were based in Adams (1998). The found results that, in group: (a) D10=12,00 and SQTL=123, (b) for the types of drawings, A=2,1%; L=64,7% and W=33,2%, (c) the profile somatotypic of the group was classificated by meso-balance, the values was 2,33 - 4,11 - 2,81, (d) the values suggested for the torque isokinetic in the different intervals among the repetitions 1-3 and 48-50, were respectively, 348,67±24,4% and, 150±24,7%, (e) doesn't exist significant difference for a value of p<0,0001 between the classification of the variables genotipics and fenotipics. In conclusion, it study accumulates the possibility dermatoglyphics insert in this sporting, as method prognostic that can aid, in the lower cost and, in the subject's evaluation diagnostic.